Pengelolaan Pembelajaran Pkn Berbasis Karakter Bangsa Di Sma N 1 Pulokulon Grobogan - Setiyowati, Endang; Prof. Dr. Bambang Sumardjoko, Prof. Dr. Bambang Sumardjoko (2017)
ABSBTRACT Endang Setiyowati. Q.100.1500.18. Civics Education Management Based On the National Character SMA N 1 Pulokulon Grobogan. Thesis. Graduate Muhammadiyah University of Surakarta. 2017. The purpose of this research is 1) To describe the preparation of national character-based learning civics in high school N 1 pulokulon Grobogan. 2) To describe the implementation of a national character-based learning civics in high school N 1 pulokulon Grobogan. 3) To describe the evaluation of national character-based learning civics in high school N 1 pulokulon Grobogan. The research is a qualitative research study design etnografi.Teknik data collection observation, interviews and documentation. Data analysis techniques of data collection, data reduction, data presentation, and conclusion. Test validity using triangulation. Results of the study 1) Preparation of Citizenship teachers SMA N 1 Pulokulon Grobogan in teaching civics-based character of the nation is compiling Learning Implementation Plan (RPP) based on the syllabus. Teachers enter values that match the characters in accordance with the decree and KD.2) Implementation civics lesson in SMA N 1 Pulokulon consists of three stages. That preliminary activities, core and cover. Teachers bring character values expected at each stage kegiatan.3) teachers to teach the values of character education in the nation with the aim of learning civics student can putting it into practice in daily life. Evaluation of a class XI and XII using the curriculum SBC is the realm of cognitive and affective .To use the class X 2013 judging curriculum used is the knowledge, skills and attitude, Keywords: civic education, character education, management